NEDD9 scaffolding protein expression as a negative prediction marker in non-small cell lung cancer (NSCLC) - M. V. Tikhomirova; V. V. Barmin; Yu. A. Topchu; A. M. Mazitova; E. Yu. Ratner; A. G. Sabirov; Z. I. Аbramova; A. Ya. Deneka (Сибирский онкологический журнал, 2022)
The purpose of the study was to assess the prognostic significance of a scaffolding NEDD9 protein in patients with non-small cell lung cancer (NSCLC). NEDD9 (Neural precursor cell expressed, developmentally down-regulated 9) is a scaffolding protein in many intracellular protein cascades, such as PI3K-AKT-mTOR, Ras-ERK, which play key roles in tumor progression. several studies define the regulatory role of NEDD9 in progression of several solid cancers, including non-small cell lung cancer (NSCLC), however its role as a prediction biomarker is minimally assessed. Materials and methods. In the current study quantitative immunohistochemical (IHC) approach was utilized to characterize NEDD9 expression in a cohort of NSCLC primary tumor samples (n=16), and correlative statistical analysis was performed between NEDD9 expression and a set of patients’ clinical and pathological characteristics. Results of the IHC analysis were validated using broader TCGA RNAseq dataset (n=566). Results. The study demonstrated significant difference between the expression of Nedd9 in stage iii tumors versus stages II and IV (p<0.05). Next, NEDD9 expression level was approximated to high and low (based on median h-score=56.14) and statistical survival analysis revealed a positive correlative trend between the decreased expression of NEDD9 and the decrease in the overall (OS) and progression-free survival (PFS) of the patients. Analysis of TCGA dataset harboring RNA seq data confirmed statistically significant correlation (p=0.05) between low NEDD9 expression and decreased OS. Conclusion. This study suggests that the expression of the scaffolding protein NEDD9, both at the protein and RNA levels, positively correlates with a negative prognosis in NSCLC, suggesting that it can potentially be used as a novel biomarker of disease progression. Further basic and clinical research defining the role of NEDD9 in the progression and metastasis of NSCLC are strongly warranted.